2019
DOI: 10.1001/jama.2018.19791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medication Co-payment Vouchers on P2Y12 Inhibitor Use and Major Adverse Cardiovascular Events Among Patients With Myocardial Infarction

Abstract: IMPORTANCE Despite guideline recommendations, many patients discontinue P2Y 12 inhibitor therapy earlier than the recommended 1 year after myocardial infarction (MI), and higher-potency P2Y 12 inhibitors are underutilized. Cost is frequently cited as an explanation for both of these observations. OBJECTIVE To determine whether removing co-payment barriers increases P2Y 12 inhibitor persistence and lowers risk of major adverse cardiovascular events (MACE). DESIGN, SETTING, AND PARTICIPANTS Cluster randomized cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 41 publications
2
65
0
1
Order By: Relevance
“…The aforementioned MI FREEE RCT found that free coverage for essential cardiovascular medications post-myocardial infarction increased adherence by 4 to 6% ( p < 0.001) but did not improve the primary outcome of the first major vascular event or procedure [ 20 ]. More recently, the ARTEMIS trial also found that provision of free access to P2Y 12 inhibiting anti-platelet agents for a year increased adherence by a small amount (2.3%), but there was no difference in major adverse cardiovascular events [ 63 ]. In addition, since patients are frequently taking medications that are not essential and may be harmful, decreased adherence to these medications may not lead to adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned MI FREEE RCT found that free coverage for essential cardiovascular medications post-myocardial infarction increased adherence by 4 to 6% ( p < 0.001) but did not improve the primary outcome of the first major vascular event or procedure [ 20 ]. More recently, the ARTEMIS trial also found that provision of free access to P2Y 12 inhibiting anti-platelet agents for a year increased adherence by a small amount (2.3%), but there was no difference in major adverse cardiovascular events [ 63 ]. In addition, since patients are frequently taking medications that are not essential and may be harmful, decreased adherence to these medications may not lead to adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lowering prescription copayment has also been tested in patients after MI hospitalization who were recommended to use antiplatelet therapy for 1 year. The ARTEMIS trial randomized 11 001 patients with MI across 301 US hospitals to either the intervention group where copayment vouchers were provided to eliminate the prescription costs of clopidogrel or ticagrelor for 1 year, or the usual care group without vouchers . Medication persistence, defined as patient‐reported use of P2Y12 inhibitors without a gap of 30 days or longer, was significantly higher in the intervention group compared to control after adjusting for baseline characteristics (2.3%; 95% CI, 0.4‐4.1).…”
Section: Implementation Strategies To Improve Preventive Care In Patimentioning
confidence: 99%
“…The first issue studied was patient cost: in circumstances in which patients pay for part or all of their drug cost, poor compliance has previously been attributed to this factor. In the Affordability and Real-World Antiplatelet Treatment Effectiveness After Myocardial Infarction Study (ARTEMIS), 12 301 US hospitals that enrolled 11,001 post-acute coronary syndrome patients randomized them to usual care or to co-payment vouchers for clopidogrel or ticagrelor for 1 year (median voucher value $137 for a 30-day supply). The co-primary outcomes were patient-reported persistence with P2Y12 inhibitor (defined as continued treatment without gap in use 30 days) and MACE (death, recurrent myocardial infarction, or stroke) at 1 year.…”
Section: Compliance Lessons From Non-statin Studiesmentioning
confidence: 99%